Deficiência em tela : processos de realização do corpo desviante no cinema - Sara de Oliveira Paoliello (2023)
This dissertation aims to investigate the expression of subjects with disabilities in cinema and analyze how the characteristics of these directors produce singularities in their works. Given that the disabled body is often stigmatized by its condition, and considered deviant from the normative point of view, as discussed by Lígia Amaral (1988), this work recognizes the power in this "deviation", as it enables other forms of expression. The research seeks to approach films made by people with disabilities, where this is a central part of the narrative, adopting the perspective of “self-narratives”, Margareth Rago (2013), which are born from the process of reinterpretation of subjective experiences. The aim is to understand how the participation of filmmakers with disabilities can affect the "filmic body". For this, the films "DesecrAcTION", by Estela Lapponi, and "Victor’s body", by Victor Di Marco and Márcio Picoli, are analyzed, in this context, the idea of the "unfinished gesture", Cecília Almeida Salles (2009), who emphasizes that an artistic work can be permanently reinterpreted, recreated and resignified. Thus, I seek an approximation with the directors' filmmaking processes and a dialogue between their experiences and my own, through personal and affective writing.